(3TQM GdbhGYOs - (3GdLfGMj, GdfLaj, GdeGdcj, LYaQ Hf NVQ cGTa GdZWGA, J (B1226(3g`s ((3GdgGOj Hf GdYHGS Hf Ydj Hf cGTa GdZWGAs)
(3ChdgG (B:s
(3GdMeO ddg GdPj GTJb fhQ GdhLhO ef XdeI GdYOe(B... (3CeG HYO, aEfg cGf jNJdL aj NGWQj ef GdReGf GdSGHb Cf CTQM bhGYO(B...s
(3BNQgG (B:s
(3gPG cdg ZPG cGf eLghd GdbOQ hCdG jLgd bOQg LGR HjYg HLfSgs
(3JHUQI GdeDda (B:s
(3aj SfI haGJg GNJdGa(B: 1228(3, h(B: 1227(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
(3GdCYdGe(B: (3L(B2(3, U(B124s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis